Strategi Efektif Pengeluaran Pemerintah : Mengoptimalkan Belanja Negara Dan Pembelian Barang Dan Jasa - Imelda Eka Maulia; Wahjoe Pangestoeti; Damayanti Simangunsong; Fathur Rahman Ramadhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Government spending is very important for a country's economy and the welfare of all levels of society. In this way, the government must allocate their funds very wisely for the survival of the country and society. Government spending is the result of various types of income, one of which is taxes. But when governments do not have sufficient financial resources, they will resort to forced efforts to take resources from other countries. One of the goals of the government in issuing their budget is to reduce the number of unemployed. The government also poured funds to maintain political stability. In this way the economy will develop with development goals. Moreover, spending to reduce chaos is not cheap. The purpose of using the literature method in this research is so that readers can understand this research on government spending in depth. This research is based on books and several articles circulating on the internet. The result of government spending is the prosperity of the entire society and country. Because with the release of funds from the government, the country's development will be carried out. Government spending will be used for the sustainability of the country and for the prosperity for society.